Solve the following equation
5(x-6)=4(x-5)
Solve for x
5(x - 6) = 4(x - 5)
Simplify by removing parentheses
Simplify 5(x - 6):
Distribute the 5 to each term in (x-6)
5 * x = (5 * 1)x = 5x
5 * -6 = (5 * -6) = -30
Our Total expanded term is 5x-30
Our new term is
5x - 30
Simplify by removing parentheses
Simplify 4(x - 5):
Distribute the 4 to each term in (x-5)
4 * x = (4 * 1)x = 4x
4 * -5 = (4 * -5) = -20
Our Total expanded term is 4x-20
Our new term is
4x - 20
Show our new expression:
5x-30=4x-20
Group variables
Group our variables 5x and 4x
subtract 4x from both sides
5x - 30 - 4x = 4x - 20 - 4x
Cancel 4x on the right side:
x - 30 = -20
Divide each side by 5
Group constants
Group our constants -30 and -20.
add 30 to both sides
x - 30 + 30 = -20 + 30
Cancel 30 on the left side:
x = 10
Final Answer
x = 10